Enhancement of Speech-Relevant Auditory Acuity in Absolute Pitch Possessors - Masataka, Nobuo (Frontiers in Psychology, 2011)
Abstract Absolute pitch (AP) is the ability to identify the frequency or musical name of a specific tone, or to identify a tone without comparing it with any objective reference tone. While AP has recently been shown to be associated with morphological changes and neurophysiological adaptations in the planum temporale, a cortical area in the brain involved in speech perception processes, no behavioral evidence of speech-relevant auditory acuity in any AP possessors has hitherto been reported. In order to seek such evidence, in the present study, 15 professional musicians with AP and 14 without AP, all of whom had acquired Japanese as their first language, were asked to identify isolated Japanese syllables as quickly as possible after these syllables were presented auditorily. When the mean latency to the syllable identification was compared, it was significantly shorter in AP possessors than in non-AP possessors whether the presented syllables were those used as Japanese labels representing the 7 tones constituting an octave or not. The latency to hear the stimuli per se did not differ according to whether the participants were AP possessors or not. The results indicate the possibility that possessing AP provides one with extraordinarily enhanced acuity to individual syllables per se as fundamental units of a segmented word in the speech stream.